Study of SREBP1 and SERBP2 in peripheral blood mononuclear cells fron hypercholesterolemic rabbits - Saez, Aldana (2019)
Peripheral blood mononuclear cells are a possible biomarker that could reveal molecular alterations before the development of the disease. Therefore, the objective of the present investigation is to study molecular and genetic changes that indicate metabolic modifications even with normal biochemical values. SERBP1 and SERBP2 are proteins involved in lipid metabolic. These molecules can be expressed in peripheral blood mononuclear cells. This allows study tissue changes without resorting to biopsies. In this study, one control group of New Zealand rabbits was fed with a balanced feed (C) and another group received the same balanced feed supplemented with 17% fat (F). These animals did not receive fructose overload, maintaining constant concentrations of carbohydrates and protein in both groups. In biochemical tests from both groups were observed similar levels of glucose (C group: 140.7 + 28.4 mg/dl / F group: 118.3 +12.0 mg/dl) and triglyceride (C group: 144.1 +15.5 mg/dl / F group: 135.6 +8.3 mg/dl), while F group showed increased levels of cholesterol (42.8 +21.6mg/dl) compared with C group (27.1 +4.5 mg/dl). However, there is variability in the cholesterol values because some animals of the F group do not experience significant increment despite the intake of fat. This interesting finding leads to the hypothesis that changes in lipid metabolism can be examined by the expression of different genes early. As preliminary results, we observed by immunohistochemistry the presence nuclear of SREBP1 and SREBP2 in lymphocytes of the F group, while in C group was not observed immunoreaction or cytoplasmic signal. This result is indicating an activation of the lipid metabolism before being able to observe changes at a biochemical level.